Aeromagnetic data to probe the Dharwar craton - Anand, S.P.; Rajaram, M. (My University, 2002)
Degree-sheet aeromagnetic maps of Dharwar craton were digitized closely along contours and re-gridded at 2.5 km interval to obtain an image map, after removal of International Geomagnetic Reference Field. The total field anomaly and generated analytical signal maps confirm the division of Dharwar craton into western and eastern blocks, and are consistent with the several strike trends of the causative sources. The Chitradurga schist belt appears to divide the Dharwar craton into the western and eastern blocks. From the present study we find that the density of the anomalies in the Eastern Dharwar is greater than that in the Western Dharwar. This may be explained by either or a combination of the following: higher grade of metamorphic rocks in the Eastern Dharwar or the Eastern block may be uplifted with respect to the Western block with the characteristics of the deeper crustal layer now exposed due to erosion or presence of thick sedimentary sequence in the Western with volcanic in the Eastern.
Keywords: Aeromagnetic data; Geomagnetic field; Dharwar craton